THE EFFECTIVENESS OF THE ORGANIZATION OF THE EXTRA CURRICULAR ACTIVITY "YOUNG ENGINEERS" - Sultonov Safar Nabiyevich (Galaxy International Interdisciplinary Research Journal, 2021)
Extracurricular activities include: Engineering Graphics Circles, Nights, Engineering Graphics Weekly, Quizzes, Contests, Posters, Preparation and Drawing Geometry, Working with Additional Literature on Mechanical Drawing, etc. Excursions to various manufacturing enterprises, design institutes and other facilities, various activities on student design creativity, the latest types of Olympiads, conferences, through which the formation of all basic competencies are described.